2020
DOI: 10.1111/ijpo.12696
|View full text |Cite
|
Sign up to set email alerts
|

Significance of autoantibody seropositivity in children with obesity and non‐alcoholic fatty liver disease

Abstract: Background: Autoantibodies are frequently positive in adults with nonalcoholic fatty liver disease (NAFLD) without concurrent autoimmune hepatitis (AIH). The clinical significance of this is unknown in children. Objective: To determine the prevalence of autoantibody positivity in pediatric NAFLD and to evaluate its association with disease severity. Methods: Multicenter, retrospective study of patients ≤18 years of age with biopsy-confirmed NAFLD. Descriptive statistics were used and groups were compared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Patton et al (6) showed that ASMA positivity increased in parallel with increasing NAS and remained an independent predictor after multivariable analysis. Yodoshi et al (7) showed that children with autoantibody positivity had lower aminotransferase levels, but those with positive ANA were more likely to have severe steatosis; otherwise, there were no associations with histologic severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patton et al (6) showed that ASMA positivity increased in parallel with increasing NAS and remained an independent predictor after multivariable analysis. Yodoshi et al (7) showed that children with autoantibody positivity had lower aminotransferase levels, but those with positive ANA were more likely to have severe steatosis; otherwise, there were no associations with histologic severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Article quality was evaluated by two researchers according to the assessment scale recommended by the Agency for Healthcare Research and Quality (AHRQ), which was suitable for cross-sectional/prevalence studies and encompassed 11 items with a maximum score of 11 points [22]. The quality of the literature was categorized as low quality (0-3), moderate quality (4-7), and high quality (8)(9)(10)(11).…”
Section: 3mentioning
confidence: 99%
“…Of these full-text articles, 4 were excluded for not providing necessary data, 3 were excluded because NAFLD in those studies was not diagnosed by liver biopsy, and 1 was excluded because the authors adopted their own higher cutoff value to define ANA positivity. Thus, 13 articles consisting of 2331 patients with NAFLD were included in the final meta-analysis (Figure 1) [11][12][13][14][23][24][25][26][27][28][29][30][31]. Table 1 outlines the detailed characteristics of the 13 included articles.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations